IMPROVEMENT OF PERSONNEL POLICY IN A PLANT DUE ADVERSE FACTORS ERMAKOV K.S., KYSAKIN A.M., A.V. MYHAMADIEVA - K. S. Ermakov; A. M. Kusakin; A. V. Muhamadieva (Научный вестник МГТУ ГА, 2016)
Provision of civil aviation enterprises the necessary human resources and their rational use, high levels of labor productivity of services and increase efficiency. The modern market dictates the need for more rational use of labor resources and more reliable method of staff monitoring.